Spatio-temporal dynamics of agricultural land use and land use change in Selangor, Malaysia using Dyna-CLUE model - Olawale, Olaniyi Akeem (2013)
Selangor is one of the most economically developed states in Malaysia. For some decades now, the contribution of the agricultural sector to the economy of the state had been overtaken by the manufacturing and the services sectors. Therefore, it becomes important to assess the trend, the drivers and predict future agricultural land uses under different scenarios and evaluate the implications of the agricultural land use change for food security. Data applied in this study were collected from the relevant agencies of the Malaysian government and the data were transformed into the formats that made them suitable for statistical analysis with excel spreadsheet, ArcGIS 9.2, MatLab and SPSS (version 19) softwares. Eighty eight spatially explicit independent variables hypothesized to influence agricultural land use decision in the study area were disaggregated from where twenty eight most significant variables driving agricultural land use were selected. Principal Component Analysis (PCA) was used to aggregate the 28 independent variables into seven important factors influencing agricultural land use decision. Scenarios of agricultural land use demands were projected with trend analysis using data of 1990 as the baseline. DynaCLUE model was utilised to allocate different agricultural land use demands under two separate spatial policies (restricted and unrestricted agricultural land use policies). The performance of the model (DynaCLUE) was evaluated with the use of Kappa statistics. Hotspots of agricultural land use change were mapped and the food security scenarios were assessed. This study found that agricultural land use in the study area will continue to decline until 2030 except under RED scenario. The agricultural land use in the study area were determined by urbanization, availability of agricultural labour, aging, sectoral competition for labour, climatic factors, accessibilities and availability of suitable agricultural land. Moreso, this research found peat swamp in the north eastern part and coastal areas of Selangor as the hotspots of land use change under the Business – as – Usual/Rapid Economic Development and Environmental Conservation scenarios respectively and that food security will be mostly assured under RED scenario. Though the ECs scenario could be attractive because of its positive impact on environment, however, it choice as an economic pathway may be unfavourable because of its social and economic implications. Whereas, the RED scenario signifies improvement in the general well being of the citizen but could cause negative impact on the sensitive ecosystems. In conclusion, this research has been able to predict the trend,identify the drivers and hotspots of agricultural land use change and assess the food security implication of different developmental scenarios in the study area.